Hadis Misoginis dan Pengembangan Masyarakat Islam Perspektif Fatima Mernissi - Rizal Faturohman Purnama (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Misogynistic hadiths that are read through gender reading are an effort to reveal models of understanding hadiths that are indicated by gender bias. This greatly affects the potential that exists in women. Therefore, opening up various modes of understanding in the community in gender studies is very important to obtain justice and provide a new color in the development of Islamic society through the eyes of the integration of science interconnections. The purpose of this paper is in addition to existing studies on the thought of Fatima Mernissi, how misogynistic hadiths are in the perspective of Fatima Mernissi. Accordingly, three questions can be formulated: (1) What is the thought of misogynistic hadiths according to Fatima Mernissi (2) Why are there misogynistic traditions. (3) How is the transformation of misogynistic traditions from feminist issues to scientific integration-interconnection towards the development of Islamic society. This study uses themethod library research (library study) using qualitative data collection techniques and descriptive-analytical approaches. The results of this study indicate that the gender relations contained in the misogynistic traditions are an attempt to reread these traditions with a gender perspective that sees more moral ideals in understanding the traditions of the Prophet. Misogynistic hadith with a gender perspective is able to provide empowerment to women, as well as social awareness as a socio-cultural issue.